Polyphenols delivery by polymeric materials: challenges in cancer treatment. (1st January 2017) - Vittorio, Orazio; Curcio, Manuela; Cojoc, Monica; Goya, Gerardo F.; Hampel, Silke; Iemma, Francesca; Dubrovska, Anna; Cirillo, Giuseppe
Abstract: Nanotechnology can offer different solutions for enhancing the therapeutic efficiency of polyphenols, a class of natural products widely explored for a potential applicability for the treatment of different diseases including cancer. While possessing interesting anticancer properties, polyphenols suffer from low stability and unfavorable pharmacokinetics, and thus suitable carriers are required when planning a therapeutic protocol. In the present review, an overview of the different strategies based on polymeric materials is presented, with the aim to highlight the strengths and the weaknesses of each approach and offer a platform of ideas for researchers working in the field.